2003
DOI: 10.1136/bmj.327.7422.1014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the critical care outreach team on patient survival to discharge from hospital and readmission to critical care: non-randomised population based study

Abstract: Objectives To determine the effect of the critical care outreach team on patient survival to discharge from hospital after discharge from critical care and readmission to critical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
164
3
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(177 citation statements)
references
References 16 publications
4
164
3
6
Order By: Relevance
“…15,16,[22][23][24] The randomized controlled trial conducted by Ball and colleagues 7 in the United Kingdom found improved outcomes after an outreach service was introduced. The LOS and readmissions before the intervention, however, were higher than those reported in Australian centers, and this difference may explain why the study by Ball et al showed a positive result.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…15,16,[22][23][24] The randomized controlled trial conducted by Ball and colleagues 7 in the United Kingdom found improved outcomes after an outreach service was introduced. The LOS and readmissions before the intervention, however, were higher than those reported in Australian centers, and this difference may explain why the study by Ball et al showed a positive result.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital survival in ICU patients was increased by 6.8% (relative risk 1.08, 95% CI, 1.00-1.18), although the difference was not statistically significant. 7 The characteristics of the "before" and "after" cohort of ICU patients in that study did not differ significantly, thus reducing the likelihood that the improvements in outcomes were due to confounding. In a more recent multicenter survey of 108 units in the United Kingdom, the critical care outreach service was associated with significant decreases in the proportion of patients admitted to the ICU who had received cardiopulmonary resuscitation before admission (95% CI, 0.73-0.96), in after-hours ICU admissions (95% CI, 0.84-0.97), and in mean physiology score 9 (95% CI, 0.31-2.12) but neither ICU mortality (95% CI, 0.87-1.08) nor in-hospital mortality changed significantly.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experience of participants in this study (for instance, see the section on coping in the broader environments) revealed the importance of careful discharge planning, post-ICU follow-up, and continuity of care in the community in enhancing patients' recovery and in addressing the special needs of their MFCs when they are required to care for their loved ones after discharge (Burr, 2002;Chaboyer et al, 2002;McCallum et al, 1996;Pearson et al, 2004). Although evaluation and searches for substantive evidence of such follow-up care like the critical care outreach service (CCOS) have been conducted by various researchers and their effectiveness is being debated (Ball et al, 2003;Cuthbertson, 2003Cuthbertson, , 2007Esmonde et al, 2006;Gao et al, 2007;Garcea et al, 2004;Priestley et al, 2004;Prinjha et al, 2009), nurses should not underestimate the value of CCOS as indicated by the experiences of patients and their MFCs in this study. According to Deacon (2008) and Whiting and Edbrooke (2006), it is recommended that continuing work or further evaluation be established in hospitals to employ or deploy specialist intensive care nurses to conduct wider ICU follow-up care, e.g.…”
Section: Diagrammentioning
confidence: 99%